Cervical Radiculopathy Impact Scale: Translation, cross-cultural adaptation, reliability and validity of the Turkish version - Alp Eren Çelenlioğlu; Savaş Şencan; Rekib Saçaklıdır; Ekim Can Öztürk; Osman Hakan Gündüz (Archives of Rheumatology, 2022)
Objectives: The aim of this study was to translate and cross-culturally adapt the English version of the Cervical Radiculopathy Impact Scale (CRIS) and to investigate the validity and reliability of the Turkish version of the CRIS. Patients and methods: Between October 2021 and February 2022, a total of 105 patients (48 males, 57 females; mean age: 45.4±11.8 years; range, 36.5 to 55.5 years) who were diagnosed with cervical radiculopathy due to disc herniation were included. Disability and quality of life were evaluated with the Neck Disability Index (NDI), Quick Disabilities of the Arm, Shoulder and Hand (QuickDASH), and Short Form-12 (SF-12). Pain severity was evaluated using the Numerical Rating Scale (NRS) in three subscales (neck pain, pain radiating to the arm, and numbness in the finger, hand, or arm). The internal consistency for CRIS was assessed using the Cronbach alpha and test-retest reliability by intraclass correlation coefficients (ICCs). Explanatory factor analyses were performed for construct validity. To examine the content validity, the correlations among the three subgroup scores of CRIS and the other scale scores were analyzed. Results: The internal consistency of CRIS was found to be high (α=0.937). A high reliability was obtained for test-retest reliability for the three subscales of CRIS (Symptoms, Energy and postures, Actions and activities) (ICC: 0.950, 0.941, 0.962, respectively; p<0.001). All three subscale scores of CRIS were correlated with the NDI, QuickDASH, SF-12 (physical and mental) and NRS scores (r=0.358-0.713, p<0.001). Factor analysis showed that the scale had five factors. Conclusion: The CRIS is a valid and reliable instrument for Turkish patients with cervical radiculopathy due to disc herniation.